The Anthem companion to Weber - Sica, Alan, 1949- (London : Anthem Press, 2016)
<The Anthem Companion to Max Weber is a study of the ideas and career of the German sociologist and founder of classical social theory. Including contributions by accomplished Weber scholars, this companion provides the latest scholarly interpretations of the sociologist$1 (Bs vast body of socioeconomic and political writings which continue to inspire new scholarship and debate on global politics, comparative religion, social class relationships, social science methods and law and society. This book serves as a handy introduction for beginners and a tidy commentary for advanced scholars.s
Notes on contributors -- Alan Sica : Max Weber invents himself -- Lutz Kaelber : Weber's dissertation and habilitation -- Christopher Adair-Toteff : Max Weber and the "agrarian crisis" 1892-1902 -- David Norman Smith : charisma and the spirit of capitalism -- Stephen Kalberg : Max Weber's sociology of civilizations : a preliminary investigation into its major methodological concepts -- Stephen Turner : Weber's foray into geopolitics -- Larry Scaff : Max Weber in the United States -- Sven Eliaeson : Weber on Russia's long road to modernity -- Jack Barbalet : the religion of China and the prospects of Chinese capitalism -- Joshua Derman : politics without magic : Weber in Weimar Germany -- Terry Maley : Weber and political theory today -- Index.
Title from publisher's bibliographic system (viewed on 11 Aug 2017).
Keywords: Weber, Max, -- 1864-1920 -- Political and social views; Sociology -- Philosophy